Republic of Poland (International Monetary Fund, 2022)
The Polish economy has rebounded strongly, with policy actions limiting the damage from the pandemic-induced recession by supporting employment and avoiding unnecessary bankruptcies. While the pandemic continues to take a toll on lives, the economy has been less impacted by successive waves of the pandemic
10.5089/9798400203688.002
Keywords: Graue Literatur; Deal package; financial asset; NBP in cooperation; state budget; rising prices; COVID-19; Government finance statistics; Global; Central and Eastern Europe; Eastern Europe; Europe; Inflation; Loans; Mortgages; International Agreements and Observance; International Organizations; Monetary Policy; Labor; Diseases: Contagious; Statistics; Industries: Financial Services; Price Level; Deflation; Data Collection and Data Estimation Methodology; Computer Programs: Other; Banks; Depository Institutions; Micro Finance Institutions; Money and Monetary Policy; Health Behavior; Demand and Supply of Labor: General; Monetary economics; International institutions; Macroeconomics; Econometrics & economic statistics; Finance; Infectious & contagious diseases; Public finance & taxation; International organization; Health; Economic and financial statistics; Financial institutions; Monetary policy; International agencies; Prices; Communicable diseases; Finance; Statistics; International Economics